2018
DOI: 10.1097/inf.0000000000001877
|View full text |Cite
|
Sign up to set email alerts
|

Nonprimary Maternal Cytomegalovirus Infection After Viral Shedding in Infants

Abstract: Nonprimary CMV infection was common in mothers after primary infection in their infants, consistent with infant-to-mother transmission. Because infants frequently acquire CMV from their mothers, for example, through breast milk, this suggests the possibility of "ping-pong" infections. Additional research is needed to characterize the antigenic and genotypic strains transmitted among children and their mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 39 publications
(41 reference statements)
2
36
0
Order By: Relevance
“…Although oral shedding by household contacts did not appear to be relevant for infant acquisition of CMV in this setting, we posit that there is a relationship between the CMV viral load of an exposure and transmission. We did not collect breast milk from mothers in this cohort, but others have reported a positive correlation between the viral load in breast milk and the risk of infant CMV acquisition [22,43,44], and we have shown a dose-response between oral CMV viral load shedding by young children and transmission to their mothers [45]. Breast milk does not appear to be a route of HHV-6 transmission [24]; rather, saliva has been thought to be the major source of HHV-6 transmission based on the frequency of viral detection in saliva [3], which our data strongly support.…”
Section: Discussionmentioning
confidence: 90%
“…Although oral shedding by household contacts did not appear to be relevant for infant acquisition of CMV in this setting, we posit that there is a relationship between the CMV viral load of an exposure and transmission. We did not collect breast milk from mothers in this cohort, but others have reported a positive correlation between the viral load in breast milk and the risk of infant CMV acquisition [22,43,44], and we have shown a dose-response between oral CMV viral load shedding by young children and transmission to their mothers [45]. Breast milk does not appear to be a route of HHV-6 transmission [24]; rather, saliva has been thought to be the major source of HHV-6 transmission based on the frequency of viral detection in saliva [3], which our data strongly support.…”
Section: Discussionmentioning
confidence: 90%
“…Leukocyte infiltrates have been characterised during this period [36], and may be the source of reactivated virus. A study conducted in Uganda has shown that mothers can be infected with strains from children [37]. However, even though multiple-strain infections were common in the cohort, there was limited evidence for reinfection or reactivation during the 4-16 week period postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers with earlier excretion of infectious virus, higher CMV milk viral loads and longer duration of excretion, are more likely to transmit CMV 26--28 . An intriguing recent study from Uganda suggested that infant--to--mother transmission of CMV can also occur, such that infants first acquire primary CMV, either from another child in the house or from their mother through breastfeeding, and then transmit the infection to their mother 29 .…”
Section: CMVmentioning
confidence: 99%